Retorque de parafusos de pilares protéticos com recobrimento de carbono tipo diamante: uma análise da manutenção do torque após fadiga mecânica - Canavezi, Rafaela Cristiane [UNESP] (2015)
The study analyzed the torque maintain of the screw abutments, with coating of diamond-like carbon (DLC) and doping of diamond (CD-DLC), submitted the retorque in external hexagonal (EH) and internal (IH) connections; after mechanical fatigue. HE and HI implants and different treatments of the abutments screws were divided into experimental groups (n = 5): untreated and not subjected to fatigue (EH-CON) (IHICON); fatigued untreatment (EH-CONF) (IH-CONF); fatigued with DLC (EH- DLCF) (IH-DLCF) and fatigued with CD-DLC (EH-CD-DLCF) (IH-CD-DLCF). The DLC and CD-DLC coating was deposited by plasma, PECVD method. Samples (Implant + abutment screew + metal crown), which had been exposed to 1 million fatigue cycles were retorquiadas, digital torque wrench, to the torque recommended by the manufacturer 30 N (HE) and 20 N (HI), and submitted again to 1 million cycles mechanics. At the end of fatigue, the screws were destorquiados to check the maintenance of torque. Screws from each experimental group were selected for observation by SEM. Statistical analysis was performed by ANOVA 2 Factors test (α = 0.05). There was no interaction among the factors studied (p = 0.765); the treatment of screws (p = 0.638) and the connection type (p = 0.615) showed no statistical difference. The microscopy images showed damage the threads and covering the presence of HI connections. Changes such as damage on the screws threads and film removal were observed among the experimental groups. The coating groups showed little or no damage on the screws threads. The DLC and CD-DLC coating did not interfere in the screw adaptation on the implant. Abutments screew coating with DLC and CD-DLC, after retorque, no raised torque maintenance